Penggunaan Media Pembelajaran Kartu Domino Matriks Untuk Meningkatan Hasil Belajar Matematika Peserta Didik - Dini Silikon (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research was motivated by the low mathematics learning outcomes of MA Negeri 1 Serang students. So it is necessary to implement learning media that helps improve students' mathematics learning outcomes. One of the learning media used is Matrix Domino Cards. This research aims to determine the learning outcomes of students who received treatment using domino matrices and students who were not given learning treatment using domino matrices. The research results show that the learning outcomes of students who were treated using matrix domino card media were higher than the learning outcomes of students without using matrix domino card media. The results of statistical tests show that students' interest in learning using domino matrix media in the experimental class obtained an average = 67.78 and standard deviation = 20.88, while learning without using domino matrix media in the experimental class obtained data on the average interest in learning of participants students = 49.72 and standard deviation = 15.48, then after carrying out the t test the results were obtained that tcount > ttable, namely 1.80 > 0.354. Hypothesis testing results obtained were tcount > ttable, so ha was accepted, meaning there was an increase in student learning outcomes using domino matrix learning media in class XI MA Negeri 1 Serang Academic Year 2022/2023.